Examining the Central and Peripheral Processes of Written Word Production Through Meta-Analysis - Purcell, Jeremy; Turkeltaub, Peter E.; Eden, Guinevere F.; Rapp, Brenda (Frontiers in Psychology, 2011)
Producing written words requires “central” cognitive processes (such as orthographic long-term and working memory) as well as more peripheral processes responsible for generating the motor actions needed for producing written words in a variety of formats (handwriting, typing, etc.). In recent years, various functional neuroimaging studies have examined the neural substrates underlying the central and peripheral processes of written word production. This study provides the first quantitative meta-analysis of these studies by applying Activation Likelihood Estimation methods (Turkeltaub et al., 2002). For alphabet languages, we identified 11 studies (with a total of 17 experimental contrasts) that had been designed to isolate central and/or peripheral processes of word spelling (total number of participants = 146). Three ALE meta-analyses were carried out. One involved the complete set of 17 contrasts; two others were applied to subsets of contrasts to distinguish the neural substrates of central from peripheral processes. These analyses identified a network of brain regions reliably associated with the central and peripheral processes of word spelling. Among the many significant results, is the finding that the regions with the greatest correspondence across studies were in the left inferior temporal/fusiform gyri and left inferior frontal gyrus. Furthermore, although the angular gyrus has traditionally been identified as a key site within the written word production network, none of the meta-analyses found it to be a consistent site of activation, identifying instead a region just superior/medial to the left angular gyrus in the left posterior intraparietal sulcus. In general these meta-analyses and the discussion of results provide a valuable foundation upon which future studies that examine the neural basis of written word production can build.